Teacher Performance Management for Enhancing Learning Quality in Primary Schools - B Burhanudin; Iim Wasliman (CV. Media Digital Publikasi Indonesia, 2025)
The improvement of learning quality in primary schools is often constrained by the lack of an integrated and sustainable teacher performance management system. This study aims to analyze the implementation of teacher performance management in realizing learning quality through four main management functions: planning, organizing, implementation, and evaluation–monitoring. This research employed a qualitative approach with a case study design conducted at SDN 1 Situsari and SDN 2 Situsari. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that both schools have implemented teacher performance management systematically, collaboratively, and with a strong orientation toward learning quality. Planning was conducted participatively and based on teacher needs; organizing emphasized clear roles and cross-functional coordination; implementation was carried out through lesson study, peer mentoring, and micro-coaching; while evaluation was conducted formatively and continuously through structured reflection and teacher portfolios. The success of these processes was supported by distributed instructional leadership and a collaborative professional learning culture (KKG/PLC). The implications of this study suggest that effective teacher performance improvement is influenced by the synergy between school management, instructional leadership, and teachers’ reflective culture. A participatory, data-driven, and collaborative management model can serve as a framework for developing sustainable teacher professional development policies to enhance learning quality in primary education.